Routine outcome measures in Germany - Puschner, Bernd; Becker, Thomas; Bauer, Stephanie (International review of psychiatry, 2015)
The German healthcare system offers comprehensive coverage for people with mental illness including inpatient, day hospital and outpatient services. These services are primarily financed through the statutory health and pension insurances. According to legal regulations, providers are required to base their services on current scientific evidence and to continuously assure the quality of their services. This paper gives an overview of recent initiatives to develop, evaluate and disseminate routine outcome measurement (ROM) in service settings in Germany. A large number of projects have shown outcome monitoring to be feasible, and that feedback of outcome may enhance routine care through an improved allocation of treatment resources. However, none of these initiatives have been integrated into routine care on a nationwide or trans-sectoral level, and their sustainability has been limited. This is due to various barriers in a fragmented mental health service system and to the lack of coordinated national or state-level service planning. The time is ripe for a concerted effort including policy-makers to pick up on these initiatives and move them towards wide-spread implementation in routine care accompanied by practice-oriented research including service user involvement.
Gesehen am 16.07.2020